2016
DOI: 10.1080/01694243.2016.1184402
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marble powder as a partial replacement of cement on some engineering properties of self-compacting concrete

Abstract: civil engineering laboratory, university of laghouat, laghouat, algeria ABSTRACT Self-compacting concretes (SCC) are highly fluid concretes that can flow and be placed in formwork under their own weight without the requirement of internal or external energy. This fluidity is obtained with the use of high paste volume and superplasticizer. The paste of SCC is made principally of cement, which is the most expensive component of concrete. As a result, the production cost of SCC is higher than conventional concret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…The apparent density and compressive strength decrease while the porosity increases.These by-products are present in the environment and contribute to pollution [14,15]. The utilization of marble dust reduces the cost of cement-based material production and also decreases the costs of removing it from the environment [16].The possibility of using waste materials such as marble dust as a partial substitution in the production of mortar and concrete has often been investigated by researchers [5,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Its mechanical properties are the main aspect of the analysis.…”
mentioning
confidence: 99%
“…The apparent density and compressive strength decrease while the porosity increases.These by-products are present in the environment and contribute to pollution [14,15]. The utilization of marble dust reduces the cost of cement-based material production and also decreases the costs of removing it from the environment [16].The possibility of using waste materials such as marble dust as a partial substitution in the production of mortar and concrete has often been investigated by researchers [5,[17][18][19][20][21][22][23][24][25][26][27][28][29]. Its mechanical properties are the main aspect of the analysis.…”
mentioning
confidence: 99%
“…The UPV test depends on several parameters such as the type and the content of cement, the type and the volume of aggregates, the type of admixture, the amount of water, the initial wetting condition, and the age of curing, it also depends on the interfacial transition zone (ITZ) between aggregate and cement paste, the density and the porosity of the cement paste, and the characteristics of aggregates [1]. The UPV test performed on standard concrete is very well described in literature [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the MP that features by a micro-filler effect that helps in forming a dense mix by filling the voids [13]. While the utilization of MP in self-compacting concrete as cement replacement led to decrease the UPV values [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], it was concluded that this decrease is due to the reduction of C 3 S and C 2 S in cement paste [15] which reduces the volume of hydrated products. Other studies [2,18] have shown that the utilization of MP as cement or sand replacement has an insignificant effect on the UPV values of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of the SCC direction the researchers are paying more attention to the design of the grain size distribution of mixtures taking into account both the grain shape and the grain size distribution of fine and coarse aggregates as well as the particle size distribution of cement and mineral additives. The use of mineral additives reduces the Portland cement consumption provides the required viscosity of the mixture and also allows to increase the durability of concrete [12][13][14]. Powders based on dolomite and limestone, rock crushing waste, quartz flour, etc.…”
Section: Introductionmentioning
confidence: 99%